Adequação da assistência pré-natal em gestantes atendidas em dois hospitais de referência para gravidez de alto risco do Sistema Único de Saúde, na cidade de Recife, Estado de Pernambuco Adequacy of the antenatal care for pregnant women seen at the two references services for women with high risk pregnancies at maternity hospitals of the Brazilian Public Health System in the city of Recife, in the State of Pernambuco - Valéria Conceição Passos de Carvalho; Thália Velho Barreto de Araújo (Instituto Materno Infantil de Pernambuco, 2007)
OBJETIVOS: investigar a adequação da assistência pré-natal realizada por gestantes usuárias do Sistema Único de Saúde (SUS) da cidade do Recife, Pernambuco. MÉTODOS: estudo de corte transversal de 612 mulheres atendidas por ocasião do parto em duas unidades do SUS, referências para gravidez de alto risco no Recife, no período de junho a outubro de 2004. A avaliação do Pré-Natal foi baseada nos critérios do Programa de Humanização do Pré-Natal e Nascimento do Ministério da Saúde. RESULTADOS: a cobertura de pré-natal foi de 96,1%, sendo a média de consultas de 5,3. Apenas 38,0% das mulheres iniciaram o pré-natal até o quarto mês de gestação e realizaram seis ou mais consultas. Dentre as entrevistadas, 31% tiveram peso, pressão arterial, altura uterina e os batimentos cardiofetais aferidos em todas as consultas. A atenção pré-natal foi considerada adequada em 17,8% e não-adequada em 82,2% dos casos. CONCLUSÕES: A assistência pré-natal disponível para as gestantes na cidade do Recife, apesar de apresentar elevada cobertura, deve ser revista do ponto de vista qualitativo. OBJECTIVES: to asses antenatal care adequacy offered to pregnant women in the Brazilian Public Health System (BPHS), in the city of Recife, in the State of Pernambuco. METHODS: a cross-sectional study of 612 women seen assisted during delivery in two BPHS units, with high risk pregnancies referrals in Recife, from June to October 2004. Antenatal care assessment was based on the criteria of the Humane Antenatal and Delivery Program of the Ministry of Health. RESULTS: antenatal coverage averaged 96.1% and the median of medical visits was of 5.3. Only 38.0% of the women initiated antenatal care by the fourth month of pregnancy and made six or more medical consults. Among the respondents, 31% had weight, arterial pressure, uterine fundus height and cardiofetal heartbeats measured in all medical visits. Antenatal care was considered adequate in 17.8% of the cases and inadequate in 82.2% of the cases. CONCLUSIONS: available antenatal care for pregnant women in Recife city has ample coverage, but it should be reviewed from a quality standpoint.